The Relationship Between Generalised Joint Hypermobility and Autism Spectrum Disorder in Adults: A Large, Cross-Sectional, Case Control Comparison - Glans, Martin R.; Thelin, Nils; Humble, Mats B.; Elwin, Marie; Bejerot, Susanne (Frontiers in Psychiatry, 2022)
Autism spectrum disorder (ASD) and generalised joint hypermobility (GJH) share a number of clinical manifestations including proprioceptive impairment, motor difficulties, sensory hypersensitivity, and autonomic dysfunction. Clinical observations suggest that GJH is overrepresented in ASD. However, there are currently few systematic studies available. Knowledge about comorbidities may unfold common aetiopathological pathways underlying the association and improve the clinical management. The aim of this large, cross-sectional comparative study is to evaluate the relationship between ASD and GJH in adults. Data on joint hypermobility, symptoms associated with both hypermobility spectrum disorders (HSD) and hypermobile Ehlers-Danlos syndrome (hEDS), lifetime psychiatric diagnoses, psychiatric rating scales for ASD and attention deficit hyperactivity disorder (ADHD), and socio-demographics was collected for 199 individuals with ASD and 419 non-ASD community controls. Logistic regression models adjusting for covariates (age, sex, ethnicity) revealed a significant relationship between ASD and GJH and between ASD and symptomatic GJH, with adjusted odds ratios of 3.1 (95% CI: 1.9, 5.2; p < 0.001) and 4.9 (95% CI: 2.6, 9.0; p < 0.001), respectively. However, the high prevalence of comorbid ADHD in the study sample reduces the generalizability of the results among individuals with ASD without comorbid ADHD. Possibly, an additional ADHD phenotype is the primary driver of the association between ASD and GJH. Furthermore, GJH with additional self-reported symptoms, suggestive of HSD/hEDS, showed a stronger association with ASD than did non-specified GJH, indicating that symptomatic GJH plays a greater role in the relationship than non-specified GJH does. Therefore, the current study underscores the need of careful sample subclassifications. ASD with GJH may represent a novel subgroup of ASD in terms of aetiopathology and clinical presentation. Future research should elucidate the aetiological factors behind the association between ASD and GJH and evaluate how the comorbidity of GJH affects ASD outcomes.